2018
DOI: 10.3390/su10020308
|View full text |Cite
|
Sign up to set email alerts
|

Economic Assessment of Flood Control Facilities under Climate Uncertainty: A Case of Nakdong River, South Korea

Abstract: Abstract:Climate change contributes to enhanced flood damage that has been increasing for the last several decades. Understanding climate uncertainties improves adaptation strategies used for investment in flood control facilities. This paper proposes an investment decision framework for one flood zone to cope with future severe climate impacts. This framework can help policy-makers investigate the cost of future damage and conduct an economic assessment using real options under future climate change scenarios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Their results showed that adopting a real-options allowing for flexibility in planning improved the economic feasibility of the investment in flood control. Furthermore, Kim and Kim ( 2018 ) modelled the volatility of returns under the RCP4.5 and RCP8.5 climate scenarios of the IPCC’s representative concentration pathway. In the considered scenarios, they showed that investments in flood control facilities that would not have been undertaken based on a NPV criterion would be undertaken if option values were taken into account.…”
Section: Real-options Analysis Of Investment In Climate Change Adaptamentioning
confidence: 99%
“…Their results showed that adopting a real-options allowing for flexibility in planning improved the economic feasibility of the investment in flood control. Furthermore, Kim and Kim ( 2018 ) modelled the volatility of returns under the RCP4.5 and RCP8.5 climate scenarios of the IPCC’s representative concentration pathway. In the considered scenarios, they showed that investments in flood control facilities that would not have been undertaken based on a NPV criterion would be undertaken if option values were taken into account.…”
Section: Real-options Analysis Of Investment In Climate Change Adaptamentioning
confidence: 99%
“…The logarithmic cash flow returns method provides volatility based on the variability of the same cash flow estimates used to calculate the underlying asset value [7]. This method has been used in several studies [7,20,[28][29][30][31][32]. Thus, we adopted logarithmic cash flow returns in our study.…”
Section: Binomial Tree Modelmentioning
confidence: 99%
“…With the development of global climate system theory, natural disasters and economic losses can now be directly predicted by future climate change scenarios. Kim et al (2017), Kim and Kim (2018) used the representative concentration pathway (RCP) climate scenarios to simulate future precipitation and rainfall disasters expected in the next 50 years. They collected historical data on the intensity of extreme rainfall and the economic losses in the affected area and proposed a loss function to predict future losses.…”
Section: Literature Reviewmentioning
confidence: 99%